Single-photon counting detectors for diffraction-limited light sources - Fröjdh, Erik; Bergamaschi, Anna; Schmitt, Bernd (Frontiers in Physics, 2024)
When first introduced, single photon counting detectors reshaped crystallography at synchrotrons.Their fast readout speed enabled, for example, shutter-less data collection and fine slicing of the rotation angle and boosted the development of new experimental techniques like ptychography.Under optimal conditions, single photon counting detectors provide an unlimited dynamic range with image noise only limited by the Poisson statistics of the incoming photons. Counting the pulses from individual photons, essentially what made the detectors so successful, also causes the main drawback which is loss of efficiency at high photon fluxes due to pulse pileup in the analog front end. To fully take advantage of diffraction limited light sources the next generation single photon counters need to improve their count rate capabilities in the same order of magnitude as the increased flux. Moreover, fast frame rates (a few kHz) are required to cope with the shorter dwell time achievable thanks to the higher flux. Detector architectures with multiple comparators and counters can open new possibilities for energy resolved imaging, while interpixelcommunication can overcome the issues arising from charge sharing and reduce the loss of efficiency at the pixel corners. Coupling single photon counting detectors to high-Z sensors for hard X-ray detection (>20 keV) as well as to Low Gain Avalanche Diodes (LGADs) for soft X-rays is also necessary to make use of the increased coherence of the new light sources over the full radiation spectrum. In this paper we present possible strategies to improve the performance of single photon counting detectors at 4th generation synchrotron sources and compare them to charge integrating detectors.